Adaptation and the new media technology: a study on Malaysian students in Australia and United Kingdom - Abdul Latiff Ahmad; Emma Mirza; Rusyda Helma Mohd; Latiffah Pawanteh; Ali Salman (Universiti Kebangsaan Malaysian, 2014)
This paper explores Lysgaard (1955) U-Curve model which explains the process of adaptation in a new culture. Lysgaard (1955) stated that those who migrate to other places go through the following stages of adaptation; the honeymoon stage, culture shock, adjustment and recovery. The existence and rise of new media technologies have brought the world closer together and thus raises the question whether one still go through the stages stated by Lysgaard (1955) New media components such as Twitter, Facebook, Skype, Blogs and Online television has created an impact towards the adaptation process. Four focus group discussions were conducted among Malaysians who had been to either Australia or United Kingdom for their tertiary education and has since returned to Malaysia. The discussions centered on the experience of these students adapting into the new culture and how the Internet and the new media has played a role through their adaptation process. Findings from the research show that the new technologies have brought them closer to their own culture and at the same time assist them in adapting into the new culture.